Improving 9th Grade Students’ Writing Competency Using Card Lottery Games Media - Suardana, I Made (STKIP AGAMA HINDU SINGARAJA, 2020)
The current study was intended to use Card Lottery Games Media to improve writing ability. The design of the study is action research. The sample of the study was IX grade students in one selected school. It was found that after implementing Card Lottery Game Media in two cycles, it could be concluded that Card Lottery Games Media was effective to improve the students’ competency in writing report text There were five aspects that should be full field by the students in writing report text, there are; developing ideas (content), organizing ideas, vocabulary, grammar, and mechanics. The students’ improvement could be seen from the mean score of the pre-test (56,25), post-test 1 (74) and post-test 2 (84,25). During the implementation of Card Lottery Games Media, the students were looked serious, enthusiastic, motivated and interested.